Hormone-switching islet cells: parallels to transmitter-switching neurons - Dor, Yuval; Spitzer, Nicholas C. (Frontiers in Cell and Developmental Biology, 2025)
Although originating from different germ layers, pancreatic islet cells and neurons share extensive similarities, both physiological (e.g., voltage-dependent release of a bioactive molecule) and molecular (e.g., highly similar composition of transcription factors and structural genes). Here we propose that two seemingly unrelated phenomena recognized in these cell types—neurotransmitter switching in neurons and the expression of two or more hormones in individual islet cells—share a deep resemblance, potentially reflecting an ancient molecular circuit of cell plasticity. Comparing and contrasting dynamic hormone expression in islet cells and transmitter switching in neurons may provide insights into the functions and underlying mechanisms of these phenomena.